Czech Republic : Report on Vision and Strategy for an Integrated Revenue Administration - World Bank (World Bank, 2012)
This report is a result of the mission of the World Bank to the Czech Republic during November 17 to 27, 2008 for providing advisory service to the Government of the Czech Republic for the design and development of a modern, integrated revenue authority. Earlier, between February and April 2008, a World Bank mission had reviewed the draft merger plan prepared by the Ministry of Finance of the Czech Republic in January 2008 and examined the key issues for the merger of tax and customs administrations and the integration of the collection, enforcement and audit functions of social contributions. The preliminary findings of the World Bank are contained in the 'report on an integrated revenue administration' in two volumes which was disseminated in June 2008. This mission in November 2008 is the first in a series of missions over the next eighteen months for providing the advisory services as requested to the Government of the Czech Republic. During this first mission, the Bank has worked with the Czech counterparts to develop for the new Jednotni Inkasni Misto (JIM): (i) an integrated vision and key concepts (ii) major objectives and key elements of reform; (iii) a comprehensive strategy for reform of the organizational structure, human resources, business processes, and information systems; (iv) project management structure; (v) change management strategy; and (vi) key performance indicators.